Identification and quantification of six major alpha-dicarbonyl process contaminants in high-fructose corn syrup - Gensberger, Sabrina; Mittelmaier, Stefan; Glomb, Marcus; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2012)
High-fructose corn syrup (HFCS) is a widely used liquid sweetener produced from corn starch by hydrolysis and partial isomerization of glucose to fructose. During these processing steps, sugars can be considerably degraded, leading, for example, to the formation of reactive aα- dicarbonyl compounds (aα-DCs). The present study performed targeted screening to identify the major aα-DCs in HFCS. For this purpose, aα-DCs were selectively converted with o-phenylendiamine to the corresponding quinoxaline derivatives, which were analyzed by liquid chromatography with hyphenated diode array-tandem mass spectrometry (LC-DAD-MS/MS) detection. 3-Deoxy-D-erythro-hexos-2- ulose (3-deoxyglucosone), D-lyxo-hexos-2-ulose (glucosone), 3-deoxy-D-threo-hexos-2- ulose (3-deoxygalactosone), 1-deoxy-D-erythro-hexos-2,3-diulose (1- deoxyglucosone), 3,4-dideoxyglucosone-3-ene, methylglyoxal, and glyoxal were identified by enhanced mass spectra as well as MS/MS product ion spectra using the synthesized standards as reference. Addition of diethylene triamine pentaacetic acid and adjustment of the derivatization conditions ensured complete derivatization without de novo formation for all identified aα-DCs in HFCS matrix except for glyoxal. Subsequently, a ultra-high performance LC-DAD-MS/MS method was established to quantify 3- deoxyglucosone, glucosone, 3-deoxygalactosone, 1- deoxyglucosone, 3,4-dideoxyglucosone-3-ene, and methylglyoxal in HFCS. Depending on the aα-DC compound and concentration, the recovery ranged between 89.2% and 105.8% with a relative standard deviation between 1.9% and 6.5%. Subsequently, the aα-DC profiles of 14 commercial HFCS samples were recorded. 3-Deoxyglucosone was identified as the major aα-DC with concentrations up to 730 μg/mL HFCS. The total aα-DC content ranged from 293 μg/mL to 1,130 μg/mL HFCS. Significantly different aα-DC levels were not detected between different HFCS specifications, but between samples of various manufacturers indicating that the aα-DC load is influenced by the production procedures. © 2012 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.identi
Keywords: α-Dicarbonyl compound (α-DC); High-fructose corn syrup (HFCS); o-Phenylenediamine (OPD); Quinoxaline derivatives; Sugar degradation products; Ultra high-performance liquid chromatography (UHPLC)